Pengaruh Model Project-Based Learning Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMP - Hikmatul Laili; Laila Hayati; Ulfa Lu'luilmaknun (Griya Journal of Mathematics Education and Application, 2026)
This study is motivated by the low level of student participation in the learning process and their limited mathematical problem-solving skills, particularly in number pattern material. The purpose of this study is to determine the effect of the Project-Based Learning (PjBL) model on the mathematical problem-solving abilities of eighth-grade students at SMP Negeri 3 Mataram. This research employed a quasi-experimental design using a posttest-only control group design. The population consisted of all eighth-grade students totaling 119 students, with a sample of 61 students selected randomly. Class VIII-1 was assigned as the experimental group using the PjBL model, while class VIII-2 served as the control group using direct instruction. Data were collected through observation and essay tests and analyzed using normality, homogeneity, and independent sample t-test, followed by effect size analysis. The results showed that the average posttest score of the experimental class (75.27) was higher than that of the control class (51.25). The data were normally distributed (Sig. experimental = 0.500 > 0.05; control = 0.096 > 0.05) and homogeneous (Sig. = 0.178 > 0.05). The t-test result indicated a significant difference (Sig. (2-tailed) = 0.000 < 0.05). Furthermore, the effect size value (Cohen’s d = 1.822) indicates a high effect, meaning that the PjBL model has a strong influence on students' mathematical problem-solving abilities. In conclusion, the Project-Based Learning model significantly improves students' mathematical problem-solving skills in number pattern material.